О двух группах периодических комет - Гулиев, А.С. (Кинематика и физика небесных тел, 1990)
Приведены результаты дополнительного исследования двух групп комет, обнаруженных в |2|. Установлены следующие их различия: 1) орбиты комет второй группы в среднем более вытянутые; 2) распределения i существенно различаются; 3) различны значения константы Тиссерана /; 4) кометы первой группы характеризуются положительной корреляцией между e и cos i. у комет второй группы такой зависимости нет; 5) рабочими узлами орбит комет первой группы в основном являются восходящие, концентрирующиеся вблизи долготы 180°, у второй — нисходящие, имеющие избыток вблизи 240°. Показано, что в общей совокупности периодических комет доминирует первая группа. The results of additional research of two groups of comets detected in [2] are given. The following differences between the groups have been established: 1) the comets of the second group have on the average larger values of eccentricity e; 2) there is a substantial difference in the distribution of i 3) the groups differ in values of the Tisscrand constant; 4) the comets of the first group have positive correlation between e and cos i, and the second group does not display a similar dependence; 5) the prime nodes of the orbits of comets in the first group are in general ascending ones, concentrating near the longitude of 180°, while in the second group they arc descending ones and have the excess near 240°. It is shown that among periodic comets the first group dominates quantitatively.